The white settlers' experience of exile and alienation in Grenville’s The Secret River - Khorzughi, Ruzbeh Babaee; Ali Termizi, Arbaayah; Jujar Singh, Hardev Kaur (Richtmann Publishing, 2015)
Literature has the capacity to create forms of history and memory that many historians and critics are not able to recognize. Kate Grenville’s The Secret River portrays the history and culture of two nations. Grenville depicts the fiction in the form of history that belongs to her own ancestors. Grenville’s novel gives her the chance to do a historical research that is from the history of her ancestors in 1805 to the realities that contemporary historians disclose about Australian settlers. In her historical fiction, Grenville depicts the exile, alienation, failure, success, dream, desire, and lifestyle of her own ancestors. Furthermore, through her novel, Grenville creates the opportunity to write on behalf of her ancestors as frontiers. In this respect, her act of writing in The Secret River is an act of revealing and solving some historical realities and mysteries with the help of the knowledge that she inherited from her own ancestors. The present study aims to explore these realities and in particular the exile and alienation of the white settlers in The Secret River.